Small Molecule Inhibitor Adjuvant Surfactant Therapy Attenuates Ventilator- and Hyperoxia-Induced Lung Injury in Preterm Rabbits - Das, Pragnya; Curstedt, Tore; Agarwal, Beamon; Prahaladan, Varsha M.; Ramirez, John; Bhandari, Shreya; Syed, Mansoor A.; Salomone, Fabrizio; Casiraghi, Costanza; Pelizzi, Nicola; Bhandari, Vineet (Frontiers in Physiology, 2020)
Background: Invasive mechanical ventilation (IMV) has become one of the mainstays of therapy in NICUs worldwide, as a result of which premature babies with extremely low birth weight have been able to survive. Although lifesaving, IMV can result in lung inflammation and injury. Surfactant therapy is considered a standard of care in preterm infants with immature lungs. Recently, small molecule inhibitors like siRNAs and miRNAs have been used for therapeutic purposes. Ddit3 (CHOP), Ang2 and miR34a are known to be upregulated in experimental lung injury. We wanted to test whether inhibitors for these molecules (CHOP siRNA, Ang2 siRNA and miR34a antagomir) if used alone or with a combination with surfactant (Curosurf®) would help in reducing ventilation and hyperoxia-induced injury in an experimental lung injury model. Methods: Preterm rabbits born by cesarean section were intratracheally instilled with the 3 small molecule inhibitors with or without Curosurf® during IMV and hyperoxia exposure. Prior to testing the inhibitors in rabbits, these small molecule inhibitors were transfected in mouse lung epithelial cells (MLE12) and delivered to neonatal mouse pups, intranasally as a proof of concept that surfactant (Curosurf®) could be used as an effective vehicle for administration of such drugs. Survival, pulmonary function tests, histopathology, immunostaining, quantitative PCR and western blotting were done to see the adjuvant effect of surfactant with these 3 small molecule inhibitors. Results: Our data shows that Curosurf® can facilitate transfection of small molecules in MLE12 cells with the same and/or increased efficiency as Lipofectamine. Surfactant given alone or as an adjuvant with small molecule inhibitors increases survival, decreases IMV and hyperoxia-induced inflammation, improves pulmonary function and lung injury scores in preterm rabbit kits. Conclusions: Our study shows that Curosurf® can be used successfully as an adjuvant therapy with small molecule inhibitors for CHOP/Ang2/miR34a. In this study, of the 3 inhibitors used, miR34a inhibitor seemed to be the most promising compound to combat IMV and hyperoxia-induced lung injury in preterm rabbits.